Numerical analysis of the influence of maximum residual thermal stresses on the intensity factor between the matrix and particle interfaces in metal matrix composite (Fracture and Structural Integrity, 2020)
A critical problem in the application of metal matrix composites is the presence of high residual thermal stresses induced during the development process. These thermally induced stresses are generally detrimental to the service life of this type of composite. This article discusses the influence of maximum residual stresses on the intensity factor. The results interpreted in terms of damage, allowed us to identify the risk zones; characterized by a significant level of maximum residual stresses (S11Max, S22Max, S33Max), namely the particle/Matrix interface.The results also show that the loading conditions and the inter-distance between matrix and particle with two interfacial cracks have an important effect on max residual stresses and stress intensity factors.
Keywords: Maximum residual stresses; Crack; intensity factor